Development of techno-pedagogy approach learning model to improve digital literation of UPN "Veteran" Jawa Timur’s students - Sholihatin, Endang; Swasti, Ika Korika; Sukirmiyadi, S; Hayati, Kinanti Resmi (International Journal for Educational and Vocational Studies, 2021)
The study objectives were 1) to describe the level of digital literacy of UPN "Veteran" Jawa Timur's  students; and 2) Developing a techno-pedagogy approach to improve digital literacy of UPN "Veteran" Jawa Timur's students. This research innovation is developing of a techno-pedagogy approach model and arranging a techno-pedagogy approach to improve students' digital literacy. This innovation is based on the idea of a pedagogical model which is an important aspect in achieving learning goals in the world of education. In the first study objective, quantitative methods are used, the second research objective uses qualitative methods. Research location at UPN "Veteran" Jawa Timur. This option is to provide insight, knowledge, and solutions to integrated pedagogical problems in learning amid the Covid-19 pandemic. Data were collected from questionnaires and in-depth interviews. Among the data needed are online skills; motivation; online video/audio; internet discussion; supporting elements;  ict abilities; blended learning models; teaching contents; frequencies of face-to-face meeting; regulation; culture.